Halal Lifestyle in Indonesia: escalation from a religious mission into a national mission - Lutfiyah, Zeni (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2023)
The purpose of this study is to find a common thread between the phenomenon of halal lifestyle and the birth of halal regulations in Indonesia. The state, as the holder of the mandate of popular sovereignty, has the authority to fulfill the right to halal and safe consumption of the people. So since the enactment of Law Number 33 of 2014 concerning Product Halal Guarantee, the government has required halal certification (mandatory) for all goods and services that enter and circulate in Indonesian territory. This research uses a qualitative method with a socio-legal research approach because the object of this research is halal lifestyle and its relation to the application of Law No. 33 of 2014 concerning Halal Product Guarantee. The results of this study indicate that the halal lifestyle is one of the important reasons for halal certification in Indonesia because this halal regulation triggers changes in people's consumption styles, not only for Muslims but is a necessity for all Indonesian people